The association between sedentary behavior, physical activity, and body composition in public and private school students aged 9 to 12 years - Hassan, Ahmed K.; Saida, Mohamed Ahmed; Hammad, Badry E. (International Journal of Innovative Research and Scientific Studies, 2025)
The study investigates the BMI-PA relation through sedentary behavior assessment among 1,500 students distributed across public (970) and private (530) school populations. The study results showed that students in public schools averaged more sedentary behavior (p = 0.027, ES = 0.113) and fewer physical activities (p < 0.001, ES = 0.268) than their peers in private schools. Students enrolled in private educational institutions experienced more cases of overweight and obesity than public school students (p = 0.041, ES = 0.11). In public schools, BMI decreased by -0.088 units per increase in physical activity (p < 0.001), yet age (p < 0.001), video gaming (p < 0.001), and laptop use (p = 0.064) as specific sedentary behaviors both showed BMI elevation. The combination of physical activity and BMI had a positive relationship in private schools (B = 0.029, p = 0.023), and laptop use (B = -0.112 to -0.125, p < 0.001); together with video gaming (B = -0.105 to -0.142, p < 0.001), it produced critical results for BMI. The characteristics of age (B = -0.008, p = 0.543) and physical activity levels (B = 0.004, p = 0.812) demonstrated no meaningful relationships with BMI measurements in private school settings.